2008
DOI: 10.1086/528682
|View full text |Cite
|
Sign up to set email alerts
|

Reappraising Transition Region Line Widths in Light of Recent Alfvén Wave Discoveries

Abstract: We provide a new interpretation of ultraviolet transition region emission line widths observed by the SUMER instrument on the Solar and Heliospheric Observatory (SOHO). This investigation is prompted by observations of the chromosphere at unprecedented spatial and temporal resolution from the Solar Optical Telescope (SOT) on Hinode revealing that all chromospheric structures above the limb display significant transverse (Alfvénic) perturbations. We demonstrate that the magnitude, network sensitivity, and appar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…Perhaps these are the ones affecting or producing the "straws" or "spicules-II" observed in Ca II H, respectively near the limb by Rutten (2006) and across the limb by De Pontieu et al (2007b), that were interpreted as Alfvén waves by De Pontieu et al (2007c). They may also explain unresolved ultraviolet line broadening (McIntosh et al 2008) and the "rapid blueshift events" at the edge of network concentrations reported by Langangen et al (2008). It is also interesting to note that the higher-temperature regions (i.e.…”
Section: Chromospheric Heatingmentioning
confidence: 98%
“…Perhaps these are the ones affecting or producing the "straws" or "spicules-II" observed in Ca II H, respectively near the limb by Rutten (2006) and across the limb by De Pontieu et al (2007b), that were interpreted as Alfvén waves by De Pontieu et al (2007c). They may also explain unresolved ultraviolet line broadening (McIntosh et al 2008) and the "rapid blueshift events" at the edge of network concentrations reported by Langangen et al (2008). It is also interesting to note that the higher-temperature regions (i.e.…”
Section: Chromospheric Heatingmentioning
confidence: 98%
“…From the fits we determine the peak intensity I p , the Doppler shift v D and the 1/e line width σ. The latter is used to determine the non-thermal line broadening σ nt with σ nt = σ 2 − σ 2 th − σ inst where σ th = 6.86 km/s (assuming a formation temperature of 80,000 K, see also McIntosh et al 2008) and σ inst = 3.9 km/s (De Pontieu et al 2014b). …”
Section: Datasetsmentioning
confidence: 99%
“…They were found in CA II H near the limb and called 'straws' by Rutten [180], observed as 'type-II spicules' in CA II H off the limb by De Pontieu et al [181,182], and identified on the disc as dark RBEs in the blue wings of Ca II 854.2 nm and Ha by Langangen et al [183] and Rouppe van der Voort et al [184]. They may also be diagnosed from extreme ultraviolet line asymmetries [185][186][187][188][189]. They are probably a key player in providing mass and energy to the corona outside active regions [190].…”
Section: (Iii) Spicules-ii/straws/rapid Blue Excursionsmentioning
confidence: 99%